Representasi Sikap Pantang Menyerah dalam Iklan Web Series Milenial "Males" Jadi Miliuner pada Kanal Youtube Smartfren Super 4G Kuota: (Analisis Semiotika Roland Barthes) - Prawiranegara, M. Ibrahim; Radjagukguk, Djudjur Luciana (Magenta | Official Journal STMK Trisakti, 2020)
Unyielding attitude is an attitude where someone is not easy to accept failure. So that the release of a Smartfren Super 4G Quota product in the Millennial web series "Males" Becomes a Millionaire intended for millennials so they don't give up easily in reaching their dreams. Advertising plays a role in shaping and determining audience decisions in deciding the purchase and use of a product and service. Advertising is one of the forms of promotion most widely used and discussed by the public, this happens because advertising has a broad reach. The research aims to find out how the Representation of Unyielding Attitude in the "Males" Millennial Web Series Advertising Becomes a Billionaire on the YouTube Channel Smartfren Super 4G Quota. The method used is a descriptive qualitative approach, through the technique of collecting data through in-depth interviews with a scriptwriter from Millennial "Males". From the results of the study note that there are signs and meanings of unyielding attitude in the form of denotation and connotation meanings and myths. The message of unyielding attitude that is, Millennial "Males" So a billionaire is still an advertisement that aims to attract the attention of the public and provide knowledge about the benefits of a product that is issued. Hadirny Atta Halilintar on the web series is expected to attract public interest in the Smart 4G Super Quota product. The main success of this Smartfren Super 4G Quota ad is that it can be seen from the large number of views on the Smartfren YouTube channel on each episode, from the first episode to the last episode always gets millions of views. ABSTRAK Sikap pantang menyerah merupakan sikap dimana seseorang tidak mudah untuk menerima kegagalan. Sehingga rilis sebuah produk Smartfren Super 4G Kuota dalam web series Milenial â€œMalesâ€ Jadi Miliuner yang diperuntukan untuk para kaum milenial agar tidak mudah menyerah dalam meraih mimpi. Iklan ikut andil dalam membentuk dan menentukan keputusan khalayak dalam memutuskan pembelian dan penggunaan suatu produk dan jasa. Iklan merupakan salah satu jenis bentuk promosi yang paling banyak digunakan dan dibahas oleh masyarakat, ini terjadi karena iklan mempunyai daya jangkauan yang luas. Penelitian bertujuan untuk mengetahui bagaimana Representasi Sikap Pantang Menyerah dalam Iklan Web Series Milenial â€œMalesâ€ Jadi Miliuner pada Kanal YouTube Smartfren Super 4G Kuota. Metode yang digunakan adalah pendekatan kualitatif yang bersifat deskriptif, melalui tehnik pengumpulan dara melalu wawancara mendalam dengan scriptwriter dari Milenial â€œMalesâ€. Dari hasil penelitian diketahui bahwa terdapat tanda-tanda dan makna dari sikap pantang menyerah yang berupa makna denotasi dan konotasi serta mitos. Pesan sikap pantang menyerah yang ada, Milenial â€œMalesâ€ Jadi Miliuner tetaplah sebuah iklan yang tidak lain bertujuan untuk menarik perhatian khalayak serta memberi pengetahuan tentang keunggulan sebuah produk yang dikeluarkan. Hadirnya Atta Halilintar pada web series tersebut diharapkan dapat menarik minat khalayak terhadap produk Smartfren Super 4G Kuota. Keberhasilan yang utama pada iklan Smartfren Super 4G Kuota ini yaitu dapat dilihat dari banyaknya jumlah views pada kanal YouTube Smartfren pada setiap episode, dari episode pertama hingga episode terakhir selalu mendapat jutaan views.